Distance, production, trade and growth: A note - Biswajit Mandal (Kiel Institute for the World Economy (IfW), 2014)
This short note tries to argue that distance is not necessarily harmful for trade. It is shown that there may be an increase in the production and volume of trade if time zones of the trading nations are non-overlapping. This implies a positive effect of distance on the volume of trade. It is also shown that exploitation of time zone difference raises welfare and ensures capital accumulation. The note builds on the emerging literature on time zones and pure theory of international trade.
Keywords: F1; 330; trade; time zone